Penerapan The 7 Islamic Daily Habits dalam Membangun Sumber Daya Manusia Berkarakter Unggul - Indah Wahyuni (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
With a very large population, Indonesia needs human resources in large quantities and quality as the main supporter in development. Experts agree that quality human resources are not only measured by skill abilities but are largely determined by their character. The results of a study at Harvard University in the United States concluded that a person's success is not solely determined by knowledge and technical abilities (hard skills), but is more determined by the ability to manage oneself and others (soft skills). This study revealed that success is only determined by about 20 percent by hard skills, the remaining 80 percent by soft skills. Even the most successful people in the world can succeed because they are more supported by soft skills than hard skills. Soft skills refer to individual brilliance in several aspects such as attitude and personality, language skills (communication), politeness, having a wide circle of friends, and being optimistic. Soft skills in the definition above are identical to character. Character is the values ​​of human behavior that relate to God Almighty, oneself. fellow human beings, the environment, and nationality that are manifested in thoughts, attitudes, feelings, words, and actions based on religious norms, law. lata kiama. culture, and customs. Character education is actually not something foreign to the religious Indonesian nation. In our State Philosophy, character education is stated in all the principles of Pancasila, stated in the national anthem with the term 'bangunlah jiwanya', and clearly stated in the National Education Law. The Law No. 20 of 2003 concerning the National Education System. Article 3 of the Law states that national education functions to develop abilities and shape the character and civilization of a dignified nation in order to educate the life of the nation. National education aims to develop the potential of students to become human beings who believe in and fear God Almighty, have noble morals, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. To fulfill these human resources, education and training have a very important role. In fact, I am of the opinion that character education is mandatory, an obligation that must be immediately implemented by the government and all parties who care about human resources.